World-Class Universities in China’s Heroic Past - Yang, Rui (International Higher Education, 2021)
China’s early modern higher education institutions achieved tremendously in terms of integrating Chinese and Western ideas of higher learning. This proves that it is possible, albeit extremely difficult, for Chinese educators to adapt a Western model of the university to the Chinese situation. As a revealing facet of modern Chinese history, this achievement has great implications for university development today and deserves much more research.